2016
DOI: 10.1007/s13105-016-0543-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs 33, 122, and 208: a potential novel targets in the treatment of obesity, diabetes, and heart-related diseases

Abstract: Despite decades of research, obesity and diabetes remain major health problems in the USA and worldwide. Among the many complications associated with diabetes is an increased risk of cardiovascular diseases, including myocardial infarction and heart failure. Recently, microRNAs have emerged as important players in heart disease and energy regulation. However, little work has investigated the role of microRNAs in cardiac energy regulation. Both human and animal studies have reported a significant increase in ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 72 publications
1
19
0
Order By: Relevance
“…Earlier studies showed that miRNA-142 (miR-142), a hematopoietic miR (14) is critical for governing T cell functions (15)(16)(17), macrophage differentiation (18), IL-6 expression in DCs (14)(15)(16), and CD4 + DC homeostasis (19). miRs have been shown to alter metabolic processes that are central to various disease processes (20)(21)(22)(23)(24)(25)(26)(27). However, it remains unknown whether miR-mediated regulation of immune responses is linked to their ability to regulate metabolic reprogramming.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies showed that miRNA-142 (miR-142), a hematopoietic miR (14) is critical for governing T cell functions (15)(16)(17), macrophage differentiation (18), IL-6 expression in DCs (14)(15)(16), and CD4 + DC homeostasis (19). miRs have been shown to alter metabolic processes that are central to various disease processes (20)(21)(22)(23)(24)(25)(26)(27). However, it remains unknown whether miR-mediated regulation of immune responses is linked to their ability to regulate metabolic reprogramming.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs can have anti-fibrotic functions, pro-fibrotic functions, or serve as MF biomarkers [ 2 , 4 ]. MiR-33a, a highly conserved microRNA ubiquitously expressed in CFs [ 5 ], is a potential therapeutic target for cardiovascular diseases because of its correlation with high-density lipoprotein cholesterol (HDL-C) [ 6 ]. Anti-miR33 therapy inhibits mitochondrial respiration and ATP production, which in conjunction with increased ABCA1 expression, works to promote macrophage cholesterol efflux and reduce atherosclerosis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the abundance of these miRNAs widely varied among the experimental samples from different mouse strains; the miRNA expression pattern in the epididymal fat of Tlr2 −/− and Tlr4 −/− mice was quite different from that in C57BL/6 and Tlr5 −/− mice. Among these miRNAs, miR-122 has recently been revealed as one of the key regulators of lipid metabolism [ 43 , 70 ]. Elevated circulating miR-122 was found be to positively associated with obesity and insulin resistance in young human adults [ 71 ] and in a murine model of obesity [ 72 ].…”
Section: Discussionmentioning
confidence: 99%